Răspuns :
Răspuns:
[tex] \frac{9}{9} + \frac{3}{9} - b = \frac{6}{9} [/tex]
[tex] \frac{12}{9} - \frac{6}{9} = b[/tex]
[tex]b = \frac{6}{9} [/tex]
[tex]d + \frac{4}{8} - \frac{2}{8} = \frac{5}{8} [/tex]
[tex]d + \frac{2}{8} = \frac{5}{8} [/tex]
[tex]d = \frac{5}{8} - \frac{2}{8} [/tex]
[tex]d = \frac{3}{8} [/tex]
1) 9/9+3/9-b= 6/9
9+3/9 -b=6/9
12/9 -b=6/9
b=12-6/9
b=6/9
2)d+4/8 -2/8=5/8
d+4-2/8=5/8
d+2/8=5/8
d+2=5
d=3
9+3/9 -b=6/9
12/9 -b=6/9
b=12-6/9
b=6/9
2)d+4/8 -2/8=5/8
d+4-2/8=5/8
d+2/8=5/8
d+2=5
d=3